GASTRO-INTESTINAL PARASITES IN WILD CARNIVORES OF WESTERN GHATS OF TAMIL NADU - R.A. Valarmathi; B. Nishanth; C. Sreekumar; P. Azhahianambi; M.G. Ganesan (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Western Ghats is a hotspot of biodiversity with different species of carnivores. The gastrointestinal parasites prevailing among free-ranging carnivores were documented by examination of forty-three (N=43) faecal samples collected in selected  regions  of  Western  ghats  by  perambulation  from  February  to  September, he study  revealed  an  overall  percentage  of     endoparasitic  infection  of about  60.46%  (n=26).  The  percentage  of  infection  of  gastrointestinal  parasites  in tiger (n=13), leopard (n=17), dhole (n=8) and golden jackal (n=5) were 38.46%, 76.47%, 75.00% and 40.00% respectively. Toxocara spp. and Taenia sp. were documented in all four carnivore species, whereas Diphyllobothrium sp. eggs were recorded  only  in  leopards.  Trichuris  sp.and  Sarcocystis  sporocyst  were  detected only in tiger samples. Strongyle eggs were recorded only in leopards and dholes.